Gambaran Kadar Kalsium pada Perokok Aktif Pekerja Buruh Bangunan di PT. Syariah Lovina Kecamatan Karangpawitan Kabupaten Garut - Astari Nurisani; Mamay Mamay; Sugiah Sugiah; Lia Mar’atiningsih; Gina Nafsa Mutmaina; Muhammad Hadi Sulhan; Meti Rizki Utari; N.Ai Erlinawati; Sandra Oktapiani (BADAN PENERBIT STIEPARI PRESS, 2025)
Calcium is the most important nutrient for bone formation and to see whether there is disease in the bones, one of which is osteoporosis. Smokers are very susceptible to osteoporosis, nicotine substances contained in cigarettes can accelerate bone absorption. In addition to bone absorption, nicotine also reduces the level and activity of the hormone estrogen in the body so that the structures of bone cells are not strong in the face of weathering. This study aimed to determine blood calcium levels in construction workers who smoke in the Karangpawitan District, Garut Regency. The type of research used is descriptive, the sample in this study is 28 people who fit the inclusion criteria and are willing to be respondents. The sample selection method uses purposive sampling. The results showed that respondents with normal calcium levels (8.2 mg/dL-10 mg/dL) totaled 24 respondents (85.8%), low calcium levels were 4 respondents (14.2%) and no respondents had high calcium levels. From the research, it can be concluded that normal calcium levels occurred in 24 respondents, low calcium levels occurred in 4 respondents, and none had high calcium levels.